The Best Indicators for Handling Negative eWOM to Improve Online Shopping Intentions - Hamdan, Hamdan; Mahaputra, M. Rizky (Jurnal Ilmu Manajemen Terapan, 2024)
This study aims to develop a conceptual model of the best aspects of responding to negative eWOM to increase online shopping intentions. This study uses SLRs explored from indexed journals, (i.e. Elsevier, Taylor and Francis, SAGE, MDPI, and Emerald), which focus on negative eWOM and online shopping intentions. Literature was obtained through the Google Scholar search engine in electronic format to make it easier to find key words. The results of this study are (i.e. (1) responding to negative eWOM can increase online shopping intentions, (2) aspects of apologize immediately, explain immediately, compensate immediately, and promises to resolve negative reviews immediately, are recognized as the best aspects in responding to negative eWOM, and (3) aspects of feel happy, feel comfortable, consider, willing to shop, continue to use, and recommend make a strong contribution in measuring online shopping intentions.